Assessing The Effectiveness of a Habit Recording Tool To Improve Mental Health of University (AUC) Students - Nounou, Noran (AUC Knowledge Fountain, 2026)
Introduction: According to previous research, the mental health of university students has become an alarming public health concern worldwide. Most of the mental disorders begin among young adults, attributed to the transition to university and increased financial and societal pressure. Despite the important effect of daily habits on mental health, there still remain research gaps in Egypt in exploring their effect among university students and exploring the potential opportunities to support their well-being. Objectives: To assess depression rates among AUC students and to evaluate the effectiveness of a newly designed habit recording board, Make an Impact (MAI) to improve depression symptoms and promote mental health among AUC undergraduate students. Methods: The study employed a mixed-method approach, by using the Patient Health Questionnaire (PHQ-9) survey to assess the depression prevalence among AUC students, and in-depth interviews to assess the effectiveness of the MAI tool in promoting mental wellness among students. Results: Key findings reveal that depression symptoms are common among graduate and undergraduate students overall. The highest proportion among the total sample and graduate students was mild depression with 33% and 41% respectively, while undergraduates showed the highest rates of moderate depression (30%). Severe depression was least common across all groups. No statistically significant differences in depression severity were found between graduate and undergraduate students (all p > 0.05). Student feedback indicated promising results for the MAI tool in building healthy habits among students. However, based on baseline depression status, there were mixed results regarding the effectiveness of the MAI tool on improving mental health status. Conclusion: The study sheds light on the mental wellness of university students, the link between habits and mental well-being, and the university students’ vulnerability to depression. The results of the current study indicate the potential benefits of building habits that support students’ mental health. The study results offer insights into the mental health status of university students while also highlighting gaps in existing support systems and recommendations for future research and mental health interventions aimed at improving the quality of life of university students.